Building a Brighter Future through the Unity of Women for National Integration - Fatima Akther (International Journal of Global Sustainable Research, 2023)
The pivotal role of women in achieving national integration cannot be overstated. They constitute a significant portion of a country's populace and are indispensable in nurturing unity, strengthening societal bonds, and consequently, fostering national unity. Women actively engage in diverse domains such as education, politics, and the workforce, wielding the potential to instigate positive transformations and promote social cohesion. Furthermore, they bear the responsibility of passing down values and traditions to succeeding generations, often serving as primary caregivers within families, thus serving as vital change agents in constructing a harmonious and united society. The study delves into the multifaceted roles women undertake in advancing national integration, encompassing their involvement in civic and political affairs, educational initiatives, and community development activities. Additionally, it examines the obstacles women encounter while fulfilling these roles, encompassing social and cultural barriers, and offers recommendations for addressing these challenges. Ultimately, the paper underscores the significance of acknowledging and supporting women's indispensable role in national integration.